2012
DOI: 10.1681/asn.2012060554
|View full text |Cite
|
Sign up to set email alerts
|

Multivessel Coronary Artery Bypass Grafting Versus Percutaneous Coronary Intervention in ESRD

Abstract: Thirty to sixty percent of patients with ESRD on dialysis have coronary heart disease, but the optimal strategy for coronary revascularization is unknown. We used data from the United States Renal Data System to define a cohort of 21,981 patients on maintenance dialysis who received initial coronary revascularization with either coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) between 1997 and 2009 and had at least 6 months of prior Medicare coverage as their primary payer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
127
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 27 publications
8
127
5
2
Order By: Relevance
“…After the first 6 months, however, CABG portended improved survival. An observational study evaluating >21 000 patients with CKD and multivessel CAD undergoing PCI or CABG revealed improved 5‐year survival rates in patients who received CABG51; however, these results do not apply to patients with single‐ or double‐vessel CAD. It is important to note that this study did not take into account LV systolic dysfunction, which places patients at a higher risk of sustaining a cardiac event in the perioperative and postoperative periods.…”
Section: Cad In Patients With Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…After the first 6 months, however, CABG portended improved survival. An observational study evaluating >21 000 patients with CKD and multivessel CAD undergoing PCI or CABG revealed improved 5‐year survival rates in patients who received CABG51; however, these results do not apply to patients with single‐ or double‐vessel CAD. It is important to note that this study did not take into account LV systolic dysfunction, which places patients at a higher risk of sustaining a cardiac event in the perioperative and postoperative periods.…”
Section: Cad In Patients With Esrdmentioning
confidence: 99%
“…Several studies have shown that the implantation of a DES is associated with lower rates of target vessel revascularization compared with patients who receive a BMS. Nevertheless, the risk of restenosis with a DES in patients with ESRD compared with patients with normal renal function is still higher 51, 53, 57, 58, 59. A randomized multicenter study evaluating the efficacy of everolimus‐eluting stents versus BMSs of identical size and implanted in the same patient showed a reduction in ischemia‐driven target vessel revascularization in patients with CKD who received DESs 60.…”
Section: Cad In Patients With Esrdmentioning
confidence: 99%
“…Studies consistently show gloomy survival rates of about 70% at 1 year and about 25% at 5 years after revascularization by either surgical or percutaneous technique. 4,5 Not surprisingly, procedures occurring in the context of ACS are associated with higher mortality rates. 3 Revascularization trends in patients with CKD 5D in the United States in the past two decades have mirrored those in the general population.…”
mentioning
confidence: 99%
“…Among patients with CKD 5D with multivessel CAD between 1997 and 2009, the volume of CABG procedures was much higher, reaching a peak of about 86% in 1997, steadily dropping to a nadir of 53% in 2006, and subsequently plateauing at about 60% thereafter. 5 Conversely, DESs constituted 87% of all percutaneous coronary intervention (PCI) procedures in 2005 but tapered to about 61% in 2008 ( Figure 1B). These corroborative observations of nationwide trends have vital implications for both short-and long-term mortality rates in this population.…”
mentioning
confidence: 99%
See 1 more Smart Citation